Answer:
6x + y = -1
Step-by-step explanation:
The general slope-intercept form of the equation of a line is given as;
![y=mx+b](https://img.qammunity.org/2023/formulas/mathematics/high-school/smsb8cbft03lwblmi49nf2l6jby2ofxzws.png)
where m = slope of the line
b = y-intercept
Given the below equation of a line;
![y=(1)/(6)x-1](https://img.qammunity.org/2023/formulas/mathematics/college/6rw2w17f9qt00iyeeffc9flpmbda5zy45s.png)
we can see that the slope of the line, m = 1/6 and the y-intercept, b = -1
Any line that will be perpendicular to the above line must have a negative reciprocal of its slope. So if the slope of the given line is 1/6, then the slope of the perpendicular line will be;
![-(1)/(((1)/(6)))=-1\ast(6)/(1)=-6](https://img.qammunity.org/2023/formulas/mathematics/high-school/o406z0nc6u185cc5mmmni8fqv9vb21a4sx.png)
So the slope of the perpendicular is -6, the equation of the line can then be written as;
![\begin{gathered} y=-6x-1 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/mp3uhtm91i13k2rnh097etptvr4fr1lb44.png)
Looking at the given options in the question, we'll need to rewrite the above equation;
Let's add 6x to both sides of the equation, we'll have;
![\begin{gathered} 6x+y=6x-6x-1 \\ 6x+y=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ql0tlvk2nthp7ctaxli654fvmnupd18nnz.png)